Curse of the technology-computer related musculoskeletal disorders and vision syndrome: a study - Pandey, Rahul; Gaur, Shikhar; Kumar, Rakesh; Kotwal, Narendra; Kumar, Sanjeev (International Journal of Research in Medical Sciences, 2020)
Background: Computer Related Musculoskeletal disorders and Vision Syndrome (CRMSKVS) is defined as symptoms due to prolonged use of Visual Display Terminal (VDT). Methods: A cross-sectional observational study was done among office-workers working on computer terminal. A self-reported questionnaire was distributed and Musculoskeletal (MSK) and visual symptoms in the preceding 12 months (01 October 2017 to 30 September 2018) were taken as dependent variable. Multivariate analysis was done to identify the determinants of CRMSKVS. Results: Responses from 1193 subjects were included in the study. CRMSKVS was present in 489 cases (40.98%; males - 37.5%, females - 58.29%). The main MSK symptoms were pain/stiffness in neck (40.98%), shoulder (38.99%), lower back (35.6%) and elbow/wrist/hand/fingers (23.1%). The ocular symptoms were excessive watering (39.6%), pain (24.99), irritation (18.6%), burning/itching sensation (29.8%), redness (40.7%), blurring of vision (13.2%) and headache (40.9%). Female gender (OR-1.498(1.262-1.778)), long duration of working hours (OR-2.77(2.399-3.214)), poor break duration (OR-2.59(2.172-3.089)), excessive smart phone use (OR-2.071(1.834-2.338)), poor posture (OR-3.883(3.282-4.592)), inappropriate distance of computer screen (OR-2.173(1.829-2.582)), low height of screen (OR-1.936(1.527-2.454)), distance of keyboard (OR-3.161(2.528-3.953)) and distance of mouse (OR-5.785(3.932-8.512)) were identified as significant determinants of CRMSKVS. Conclusions: CRMSKVS is an emerging pandemic which needs urgent attention by medical and administrative authorities. The device factors, personal factors, environmental and ergonomic factors are the modifiable risk factors for CRMSKVS.